Gaucher disease type 3: genetics and phenotypes - Mistry, Pramod K. (Henry Stewart Talks, 2023)
Taxonomy of Gaucher disease type 3 (GD3), Natural history of GD3, Biomarkers of GD3, GD3 phenotype heterogeneity, Imiglucerase treatment, Unmet needs of GD3, Clinical manifestations of GD3